Imobilisasi Asam Humat Pada Kitin Dan Aplikasinya Sebagai Adsorben Cr(III) - Sehol, Muhamad; Juari Santosa, Sri; Siswanta, Dwi (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2018)
Immobilization of humic acid on chitin has been conducted and applied to the adsorption of Cr(III). The humic acid was isolated using NaOH 0.1 M, while chitin was isolated by deproteination of crab shells by using NaOH 3.5 % (w/v) and followed by demineralization using HCl 1 M. Chitin obtained from ambient-temperature-dried crab shell is named as chitin I, and crab shell washed by HOCl solution and followed by drying at ambient temperature is named chitin II. The total acidity of the humic acid was 230.95 cmol/kg, and it was distributed into the acidity of COOH 168.75 cmol/kg, and phenolic-OH 62.20 cmol/kg. Adsorbent A with chitin I as the main material and adsorbent B with chitin II as the main material, resulted the adsorbed humic acid of 9.25 and 1.68% (w/w), respectively. Adsorption of Cr(III) was maximum at pH 5, with rate of constants orde of chitin II>adsorbent B>adsorbent A>chitin I, i.e. 0.3509; ; 0.2488; 0.1553; 0.0568 minute-1, respectively. The capacity of adsorption was in the orde of chitin I>adsorbent B>chitin II>adsorbent A, i.e. 944.77; 912.53; 895.37; 893.81 mg/g, respectively. The energy of adsorption of Cr(III) of chitin II>chitin I>adsorbent A>adsorbent B, i.e. 22.932; 20,945; 20.312; 19.615 kJ/mol, respectively.